ANALYTICAL RESEARCH OF DATA CENTER SECURITY IMPLEMENTATIONS AND CYBER ATTACKS - Hardiksinh Rayjada, Dr.Vaishali Parsania (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
As the Internet is not secure; data center security can be at a threat due to any anonymous attacks. The Physical Security setup on the data center is the set of protocols within the data center facilities. Virtual security is a very hard task to handle, as there exist many ways and confidentiality Datacenter. Standard attacks are daily threats for the data centers. WAN, LAN, and HOST security require server implementing security more than seven tins to protect server attack from a virus, Hacker, and human. Data centers maintain multiple levels of security on a 24*7*365Days, Network protection, inside and outside security Firewalls, and data protection is a major critical area for security break. Servers implementing security can have more safety data.